Knowledge, Attitude, and Practice Regarding Supplemental Iron and Folic Acid Amongst Women Delivering in Edaga-Hamus Community Hospital: A Cross-Sectional Study in Asmara, Eritrea - Tsegai MB; Berhe AH; Tesfaezgi SB; Weldemariam DG; Petros KT; Weldetinsae HB; Tesfamariam EH (Dove Medical Press, 2023)
Meron Berhe Tsegai,1 Abiel Habtom Berhe,2 Semhar Berhane Tesfaezgi,3 Dawit G Weldemariam,4 Kifleyesus Tedla Petros,5 Hana Bereket Weldetinsae,3 Eyasu H Tesfamariam6 1Planning Unit, Ministry of Health, Zoba Maekel Branch, Asmara, Eritrea; 2Department of Pharmacy, Edaga-Hamus Community Hospital, Asmara, Eritrea; 3Maternal & Child Health Unit, Edaga-Hamus Community Hospital, Asmara, Eritrea; 4Department of Pharmacy, Hazhaz Zonal Referral Hospital, Asmara, Eritrea; 5Department of Obstetrics and Gynaecology, Edaga-Hamus Community Hospital, Asmara, Eritrea; 6Department of Statistics, Biostatistics and Epidemiology, College of Science, Eritrean Institute of Technology, Mai-Nefhi, EritreaCorrespondence: Meron Berhe Tsegai, Tel +291 7573197, Email meron777forever@gmail.comPurpose: In Eritrea, every pregnant woman is provided with a supplemental iron and folic acid (IFA) tablet starting from the first antenatal visit throughout the end of pregnancy. In Zoba Maekel, two-third of first antenatal visits have been at either the second or third trimesters. This practice could limit pregnant women's timely access to the nutritional supplement and its benefits. Therefore, this study aims to identify the knowledge, attitude, and practice of women delivering in Edaga-Hamus Community Hospital towards the supplemental IFA tablet.Materials and Methods: A health facility-based cross-sectional study was carried out on 360 women delivering in Edaga-Hamus Community Hospital. Data were collected using a structured questionnaire through systematic sampling. Associated factors were identified using bivariate and multivariable logistic regression. Associations with a p-value < 0.05 were considered significant.Results: Mothers with higher level of IFA knowledge and attitude held 52.8% and 65.4%, respectively. Health care workers were predominantly (92.3%) the main source for IFA information. Possible IFA side-effects were known by 64.8% of the mothers, even though only 28.2% knew reduction of side effects if taken with food. Almost all (96.1% and 97.0% respectively) believed IFA is beneficial and can prevent anemia. Only 27.9% had appropriately practiced taking the IFA supplement. Mothers who visited for antenatal care more than 8 times (AOR: 4.02, 95% CI: 1.45, 11.09) and 5 to 8 times (AOR: 2.87, 95% CI: 1.52, 5.41) had increased odds of appropriate IFA practice compared to those who visited for 1 to 4 times. Women who had planned pregnancies (AOR: 2.03, 95% CI: 1.01, 4.10) were more likely to have appropriate practice than their counterparts who had unplanned pregnancies.Conclusion: The study indicated that further strategies need to be implemented to increase the current level of knowledge, attitude, and practice of IFA.Keywords: iron and folic acid, knowledge, attitude, practice